1999
DOI: 10.1021/om9807598
|View full text |Cite
|
Sign up to set email alerts
|

Novel Routes to Bidentate Cyclopentadienyl−Alkoxide Complexes of Titanium:  Synthesis of (η5-σ-C5R14CHR2CH2CR3R4O)TiCl2

Abstract: Reaction of C5R1 4(SiMe3)CHR2CH2CR3R4OR5 with titanium tetrachloride gives the bidentate η5-σ-cyclopentadienyl−alkoxide complexes of titanium (η5-σ-C5R1 4CHR2CH2CR3R4O)TiCl2 through elimination of chlorotrimethylsilane and RCl (R = SiMe3, CH2Ph, CMe3). A potentially tridentate system (R1, R2, R3 = H, R4 = −(CH2)2OMe) was synthesized in optically pure form and its structure determined by X-ray diffraction. The pendant ether oxygen does not coordinate to the metal, and hydride transfer reactions catalyzed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 93 publications
0
16
0
1
Order By: Relevance
“…Investigation of catalyst behavior in the hydrogenation of imine prompted the synthesis of a series of titanium complexes (η 5 :η 1 -C 5 H 4 SiMe 2 NR′)TiCl 2 (142)(143)(144)(145)(146)(147)(148) and (η 5 :η 1 -C 5 Me 4 SiMe 2 NR′)TiCl 2 (149)(150)(151)(152)(153)(154)(155) [R′ ) CHMePh, CHMeC 10 H 7 , CHMeCMe 3 , CHPhCMe 3 , CHMeC 6 H 11 , (1S)-pinayl-3, or (1R)-bornyl-2] containing an enantiomerically pure linked amido-cycopentadienyl ligand in which both R and R′ were varied. 182 Following established synthetic methodologies (routes A and C), two series of titanium dichloride complexes (Sc)-(η 5 :η 1 -C 5 R 4 SiMe 2 NR′)TiCl 2 [R ) H (142)(143)(144)(145)(146)(147)(148) or Me (149)(150)(151)(152)(153)(154)(155)] with various optically active amido substituents R′ were synthesized (Chart 10).…”
Section: Mono-cp(ind) Titanium Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of catalyst behavior in the hydrogenation of imine prompted the synthesis of a series of titanium complexes (η 5 :η 1 -C 5 H 4 SiMe 2 NR′)TiCl 2 (142)(143)(144)(145)(146)(147)(148) and (η 5 :η 1 -C 5 Me 4 SiMe 2 NR′)TiCl 2 (149)(150)(151)(152)(153)(154)(155) [R′ ) CHMePh, CHMeC 10 H 7 , CHMeCMe 3 , CHPhCMe 3 , CHMeC 6 H 11 , (1S)-pinayl-3, or (1R)-bornyl-2] containing an enantiomerically pure linked amido-cycopentadienyl ligand in which both R and R′ were varied. 182 Following established synthetic methodologies (routes A and C), two series of titanium dichloride complexes (Sc)-(η 5 :η 1 -C 5 R 4 SiMe 2 NR′)TiCl 2 [R ) H (142)(143)(144)(145)(146)(147)(148) or Me (149)(150)(151)(152)(153)(154)(155)] with various optically active amido substituents R′ were synthesized (Chart 10).…”
Section: Mono-cp(ind) Titanium Complexesmentioning
confidence: 99%
“…182 Following established synthetic methodologies (routes A and C), two series of titanium dichloride complexes (Sc)-(η 5 :η 1 -C 5 R 4 SiMe 2 NR′)TiCl 2 [R ) H (142)(143)(144)(145)(146)(147)(148) or Me (149)(150)(151)(152)(153)(154)(155)] with various optically active amido substituents R′ were synthesized (Chart 10). It seems that the nature of the Cp ring is very important in determining the synthetic route; hence, the authors reported synthesizing C 5 H 4 -and C 5 Me 4 -based complexes via routes A and C, respectively (156)(157)(158)(159).…”
Section: Mono-cp(ind) Titanium Complexesmentioning
confidence: 99%
“…Chemie cyclopentadienyl ligands [25] and alkylated cyclopentadiene compounds, [26,27] polystyrene prepared by ATRP and bearing a terminal bromine substituent was treated with sodium cyclopentadienide in THF to achieve a complete substitution of the bromine atom with a cyclopentadienyl moiety (Scheme 2), as evidenced by 1 H NMR spectroscopy (see Figure S5 in the Supporting Information). Concomitantly, commercially available poly(ethylene glycol) monomethyl ether was also equipped with a cyclopentadienyl end group through nucleophilic substitution of a tosylated intermediate (Scheme 3).…”
Section: Methodsmentioning
confidence: 99%
“…The CGC with a pendent nitrogen donor on the cyclopentadienyl ligand have been widely studied for the copolymerization of ethylene with α‐olefin in both industry and academia 12–14. A considerable number of catalysts with a pendent oxygen donor on the cyclopentadienyl ligand have also been reported,15–17 but the copolymerization of ethylene with α‐olefin catalyzed by this kind of catalysts has not been systematically studied so far.…”
Section: Introductionmentioning
confidence: 99%